2020
DOI: 10.1051/0004-6361/202038952
|View full text |Cite
|
Sign up to set email alerts
|

ALMA chemical survey of disk-outflow sources in Taurus (ALMA-DOT)

Abstract: The chemical composition of planets is inherited from that of the natal protoplanetary disk at the time of planet formation. Increasing observational evidence suggests that planet formation occurs in less than 1−2 Myr. This motivates the need for spatially resolved spectral observations of young Class I disks, as carried out by the ALMA chemical survey of Disk-Outflow sources in Taurus (ALMA-DOT). In the context of ALMA-DOT, we observe the edge-on disk around the Class I source IRAS 04302+2247 (the butterfly s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 47 publications
11
67
0
Order By: Relevance
“…Its almost edge-on orientation allows us to clearly disentangle the red-(southern) and blue-shifted (northern) lobes. The systemic velocity estimated from the velocity distribution of the bright H 2 CO line is +5.6 km s −1 (Podio et al 2020a), in good agreement with IRAM 30-m CN, H 2 CO, CS, and C 17 O spectra of Guilloteau et al (2013Guilloteau et al ( , 2016. The rotation pattern has been imaged also by Podio et al (2020a), who found, using CO, H 2 CO, and CS emission, a molecular emission which is vertically stratified (see Sect.…”
Section: H 2 Cs Kinematicssupporting
confidence: 81%
See 4 more Smart Citations
“…Its almost edge-on orientation allows us to clearly disentangle the red-(southern) and blue-shifted (northern) lobes. The systemic velocity estimated from the velocity distribution of the bright H 2 CO line is +5.6 km s −1 (Podio et al 2020a), in good agreement with IRAM 30-m CN, H 2 CO, CS, and C 17 O spectra of Guilloteau et al (2013Guilloteau et al ( , 2016. The rotation pattern has been imaged also by Podio et al (2020a), who found, using CO, H 2 CO, and CS emission, a molecular emission which is vertically stratified (see Sect.…”
Section: H 2 Cs Kinematicssupporting
confidence: 81%
“…The comparison between the moment 0 distributions of H 2 CS with those of H 2 CO (Podio et al 2020a) is also instructive (see Fig. 6), showing a slightly different radial distribution of H 2 CO and H 2 CS.…”
Section: Comparison Between H 2 Cs Cs and H 2 Comentioning
confidence: 84%
See 3 more Smart Citations